2021
DOI: 10.1038/s41392-021-00793-z
|View full text |Cite
|
Sign up to set email alerts
|

HACE1-mediated NRF2 activation causes enhanced malignant phenotypes and decreased radiosensitivity of glioma cells

Abstract: HACE1, an E3 ubiquitin-protein ligase, is frequently inactivated and has been evidenced as a putative tumor suppressor in different types of cancer. However, its role in glioma remains elusive. Here, we observed increased expression of HACE1 in gliomas related to control subjects, and found a strong correlation of high HACE1 expression with poor prognosis in patients with WHO grade III and IV as well as low-grade glioma (LGG) patients receiving radiotherapy. HACE1 knockdown obviously suppressed malignant behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…A further study indicated that ionizing radiation activated ARE-dependent transcription in breast cancer cells, and the Nrf2-ARE pathway was important in maintaining resistance to irradiation under specific circumstances (30). Moreover, it was preliminarily shown that Nrf2 might enhance the resistivity to radiotherapy of specific human malignant cells including glioma (31)(32)(33). These findings led to the hypothesis that the antioxidant role of Nrf2 would be very important in the radioresistance of glioma cells.…”
Section: Discussionmentioning
confidence: 97%
“…A further study indicated that ionizing radiation activated ARE-dependent transcription in breast cancer cells, and the Nrf2-ARE pathway was important in maintaining resistance to irradiation under specific circumstances (30). Moreover, it was preliminarily shown that Nrf2 might enhance the resistivity to radiotherapy of specific human malignant cells including glioma (31)(32)(33). These findings led to the hypothesis that the antioxidant role of Nrf2 would be very important in the radioresistance of glioma cells.…”
Section: Discussionmentioning
confidence: 97%
“…Colocalization studies suggest an interaction between HTT IBs and HIP2 in SH-SY5Y cells and post-mortem brain tissue, indicating that HIP2 colocalizes with HTT (de Pril et al, 2007). While knockdown of the HIP2 protein or deletion of its catalytic domain reduced mHTT IBs and polyQ-induced cell death in SH-Sy5Y cells, overexpression of HIP2 did not affect mHTT aggregation (de Pril et al, 2007), suggesting that HIP2 is not a limiting factor in controlling mHTT aggregation. Strikingly, knockdown of HIP2 in patient-derived induced pluripotent stem cells (iPSCs) had no effect on the number of mHTT IBs (Koyuncu et al, 2018).…”
Section: Hip2mentioning
confidence: 89%
“…HACE1 is highly expressed in neuronal and glial cells and is involved in Golgi membrane fusion, the regulation of small GTPases, and protein degradation. Furthermore, HACE1 promotes the stability NRF2 (Da et al, 2021), which is an important regulator of the antioxidative stress response (Ma, 2013). Rotblat and colleagues found that HACE1 is reduced in the striatum of HD patients.…”
Section: Hace1mentioning
confidence: 99%
“…[50] In addition, ROS can activate the nuclear factor erythroid 2-related factor 2 (Nrf2)/antioxidant responsive element signaling pathway, in which mitogen-activated protein kinases, protein kinase C, and phosphatidyl alcohol-3-kinase participate in several protein kinase pathways. [52,53] In-depth mechanism exploration still needs more experiments to verify. Although the results of this study partially revealed the mechanisms underlying the ability of ZnO 0.2 -NiO@COOH to absorb ROS, the specific pathways remain unclear, thus further studies are warranted.…”
Section: Discussionmentioning
confidence: 99%